39‐3: An Electrostatic Haptic Display with a Projected Capacitive Touch Screen. Issue 1 (May 2016) - Kim, Ki Duk; Choi, Yongkyun; Yoon, Seung Hwan; Kang, Jeonggoo; Kim, Heewon; Ryu, Jeha
Abstract : This paper shows that 1 MΩ resistance of an electrostatic electrode can be used to commercialize the electrostatic tactile technology. The DC offset method induces electrostatic tactile feedback best among 3 kinds of modulation methods to reduce operational voltages, and reduces 39.9% of them in comparison with the conventional method.